Circumferential Fusion Employing Transforaminal vs. Direct Lateral Lumbar Interbody Fusion—A Potential Impact on Implants Stability - Bokov, Andrey; Kalinina, Svetlana; Leontev, Andrei; Mlyavykh, Sergey (Frontiers in Surgery, 2022)
Background: Different fusion techniques were introduced in clinical practice in patients with lumbar degenerative disc disease, however no evidence has been provided on advantages of one technique over another. The objective of this study is to assess a potential impact of circumferential fusion employing TLIF versus DLIF on pedicle screw stability. Materials and methods: This is a single-center prospective evaluation of consecutive 138 patients with degenerative instability of lumbar spinal segments. Either conventional transforaminal lumbar interbody fusion (TLIF) with posterior fusion or direct lateral interbody fusion (DLIF) using cages of standard dimensions, were applied. Conventional open technique was used to supplement TLIF with pedicle screws while percutaneous screw placement was used in patients treated with DLIF. The duration of the follow-up accounted for 18 months. Signs of pedicle screws loosening (PSL) and bone union after fusion were assessed by the results of CT imaging. Fisher`s exact test was used to assess the differences in rate of CT loosening and revision surgery because of implant instability. Logistic regression was used to assess the association between potential factors and complication rate. Results: The rate of PSL detected by CT and relevant revision surgery in groups treated with TLIF and DLIF accounted for 25 (32.9%) versus 2 (3.2%) respectively for the former and 9 (12,0%) versus 0 (0%) for the latter (p<0,0001 and p=0.0043) respectively. According to the results of logistic regression a decrease in radiodensity values and greater number of levels fused were associated with a rise in PSL rate. DLIF application in patients with radiodensity below 140 HU was associated with a considerable decrease in complication rate. Unipolar or bipolar pseudoarthrosis in patients operated on with TLIF was associated with a rise in PSL rate while patients treated with DLIF tolerate delayed interbody fusion formation. In patients treated with TLIF supplementary total or partial posterior fusion resulted in a decline in PSL rate. Conclusion: Even though the supplementary posterior fusion may considerably reduce the rate of PSL in patients treated with TLIF, application of DLIF provide greater stability resulting in a substantial decline in PSL rate and relevant revision surgery.